Diagnostic imaging of femoroacetabular impingement. - Nepple, J; Prather, H; Trousdale, RT; Clohisy, J; Beaulé, P; Glyn-Jones, S; Rakhra, K; Kim, Y (2013)
Imaging studies play a key role in establishing the diagnosis of femoroacetabular impingement (FAI). When clinical examination is suggestive of FAI, radiographic evidence should confirm the diagnosis. Imaging findings must be evaluated in the context of the patient's clinical presentation and recreational activities. Plain radiographic evaluation remains the initial diagnostic modality. Three-dimensional imaging such as MRI and CT often is obtained for the evaluation of labral and cartilage pathology, definition of bony anatomy, and surgical planning.